POLA KECERDASAN EMOSIONAL SISWA DAN BUDAYA SEKOLAH DALAM MENGHAFAL AL-QUR’AN DI MTsS FASTABIQUL KHAIRAT NAGARI GUNUNG MALINTANG KEC. PANGKALAN KOTO BARU - Wulan Say; Muhiddinur Kamal; Arman Husni; Charles (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is based on the observations results with teachers and students have a very important role, because students are the main target objects in learning, especially in reading and memorizing the Al-Qur'an. This is quite important because reading and memorizing the Al-Qur'an has a great influence on the personality of each individual. Students are children who are entering puberty, they are still very sensitive emotionally so it is not surprising that various problems arise. The problem that students often face is that some find it difficult to memorize and give up easily. The students still have minimal knowledge about memorizing the Qur'an, memorizing it, and how to continuously carry out and manage memorization. program and there is no tahfidz teacher to help students memorize it. Type of this research is descriptive qualitative research, which is the most basic form of research, aimed at describing or illustrating phenomena that exist or occur in the field. In this research the author describes the Pattern of Students' Emotional Intelligence and School Culture in Memorizing the Al-Qur'an at MTsS Fastabiqul Khairat Kenagarian Gunung Malintang. Based on the research results it can be, concluded that: Patterns of emotional intelligence and school culture in memorizing the Al-Qur'an or tahfizhul Qur'an at MTsS Fastabiqul Khairat Kenagarian Gunung Malintang. The coaching patterns carried out are tahsin coaching, recitation coaching, group coaching, and tahfiz coaching. The science of tajwid, makhorijul letters, siifatul letters, and songs or tones in reading the Al-Qur'an. Then the supporting factors in developing Qur'an learning are as follows: Strong motivation from within the students, the last MTsS Fastabiqul Khairat environmental factor is the educator and supervisor factor. And the inhibiting factors are the condition of students including laziness, sleepiness, weakening of enthusiasm and lack of human resources and limited time.